Impacts of climate change, policy and Water-Energy-Food nexus on hydropower development - Zhang, Xiao; Li, Hong-Yi; Deng, Zhiqun Daniel; Ringler, Claudia; Gao, Yang; Hejazi, Mohamad I.; Leung, L. Ruby. (Elsevier, 2018)
Hydropower plays an important role as the global energy system moves towards a less carbon-intensive and sustainable future as promoted under the Sustainable Development Goals (SDGs). This article provides a systematic review of the impacts from policy, climate change and Water-Energy-Food (W-E-F) nexus on hydropower development at global scale. Asia, Africa and Latin America are hotspots promoting hydropower development with capacity expansion, while Europe and North America focus on performance improvement and environment impacts mitigation. Climate change is projected to improve gross hydropower potential (GHP) at high latitude of North Hemisphere and tropical Africa and decrease that in the US, South Africa and south and central Europe. Analysis from W-E-F nexus highlights the importance of integrated approaches as well as cross-sectoral coordination so as to improve resources use efficiency and achieve sustainable hydropower development. These three factors together shape the future of hydropower and need to be considered for planning and operation purpose.